Assessing improvements in metastatic renal cell carcinoma systemic treatments from the pre-cytokine to the immune checkpoint inhibitor eras: a retrospective analysis of real-world data. (15th December 2020) - Ishihara, Hiroki; Takagi, Toshio; Kondo, Tsunenori; Fukuda, Hironori; Tachibana, Hidekazu; Yoshida, Kazuhiko; Iizuka, Junpei; Kobayashi, Hirohito; Okumi, Masayoshi; Ishida, Hideki; Tanabe, Kazunari
Abstract: Objective: Studies assessing outcome improvements over a long period according to systemic therapy strategies for metastatic renal cell carcinoma using real-world data, including the results of the recent era of immune checkpoint inhibitors, are limited. Herein, we retrospectively evaluated patients who were diagnosed with metastatic renal cell carcinoma over a 40-year span. Methods: Patients were classified into four groups based on when their metastases were diagnosed as follows: (i) the pre-cytokine era (1980–1986), (ii) the cytokine era (1987–2007), (iii) the molecular-targeted therapy (mTT) era (2008 to August 2016) and (iv) the immune checkpoint inhibitor era (September 2016 to 2018). The immune checkpoint inhibitor era consisted of second- or later-line nivolumab. Overall survival from the diagnoses of metastases was evaluated. Results: In total, 576 patients were evaluated, including 22 (3.82%), 231 (40.1%), 253 (43.9%) and 70 (12.2%) patients from the pre-cytokine, cytokine, molecular-targeted therapy and immune checkpoint inhibitor eras, respectively. The overall survival significantly improved with each successive era (median: 13.1 vs. 24.5 vs. 44.4 months vs. not reached in pre-cytokine vs. cytokine vs. molecular-targeted therapy vs. immune checkpoint inhibitor eras, P  < 0.0001). The implementation of molecular-targeted therapy improved overall survival compared with that of cytokine (cytokine vs. molecular-targeted therapy eras, P  < 0.0001). Multivariate analysis demonstrated that the era was an independent factor for overall survival ( P  < 0.0001), together with histopathological type; metastasis status (i.e. synchronous or metachronous); systemic therapy status (i.e. absence or presence) and bone, liver or lymph node metastasis status (all, P  < 0.05). Conclusion: This retrospective study of real-world data indicated that metastatic renal cell carcinoma outcomes improved with successive systemic therapy paradigms. Abstract : We assessed outcome change in 576 patients with metastatic renal cell carcinoma over 40-year span. The outcome improved with successive systemic therapy paradigms including an immune checkpoint inhibitor era.